Financial Determinants of Microfinance Institutions Sustainability in Nairobi County, Kenya - Kathomi, Ann (University of Embu, 2017)
Microfinance Institutions services have continued to play an important role in Kenyan economy. It is viewed as the provision of financial services to the poor and low income group. Microfinance Institutions in Kenya have gained wide recognition since 1990’s for the role they play in providing financial services to the low-income households, and their contribution to poverty alleviation. While achieving this poverty reduction goal, MFIs should also be financially sustainable. The issue of sustainability of MFIs has attracted the attention of many researchers and academicians on how MFIs can fulfill their social obligations and remain sustainable. The research assessed the effects of financial determinants of microfinance institutions sustainability in Nairobi County, Kenya. The research was guided by liquidity preference theory, theory of inflation rate, and exchange rate parity theory. The study employed descriptive survey research design. This study adopted census where all the 49 MFIs operating in Nairobi County were considered. The study relied on primary and secondary data. Primary data was collected using semi – structured questionnaires with both open and closed ended. Secondary data was collected from published audited financial statements. Pretesting of research tools was used to test reliability and validity of the questionnaires. Data was cleaned, coded, edited, classified and analyzed using Statistical Package for Social Science. The descriptive statistics tools used were mean, standard deviation, mode and variance to analyze quantitative data. Multiple regression analysis was used to establish the relationship between independent and dependent variables. The results of the analysis were presented in form of figures and tables. The study revealed that increasing the lending interest rate reduces the return thus affecting the sustainability of MFIs. In addition, the study found that high inflation rate leads to low lending power of the MFIs. The study further revealed that poor economic conditions results into high rate of foreign exchange impacting on the general investment by the MFIs. The study concluded that changes in lending interest rate by the government affect sustainability of MFIs in Nairobi County. The study concluded that inflation on MFIs sustainability indicated that lending levels are usually weak and low in the presence of higher inflation rates. The study further concluded that the premium or discount in foreign exchange impacts on the foreign capital thus the sustainability of MFIs. The study recommends that lending interest rate be regulated for sustainable microfinance Institutions. The government to implement measures to bring the inflation rate to optimal level by reducing the prices of goods and services. It is recommended that the government to implement measures to enhance the appreciation of the shilling against the foreign currencies. The study will enable the government to develop the right policies to implement to the Microfinance institutions to promote their services to the citizens and remain sustainable. The study will enable the management of microfinance institutions to understand the effect of financial determinants in their industry. Professionals advising the investors can use the study findings to inform their investors on issues involving microfinance lending and how the financial determinants affect the microfinance sector in Kenya.